2018
DOI: 10.1002/macp.201800268
|View full text |Cite
|
Sign up to set email alerts
|

Counterion Effect of Amine Salts on Ring‐Opening Polymerization of 1,3‐Benzoxazines

Abstract: The effect of nucleophilicity of counterions of amine HX salts as catalysts on the ring‐opening polymerization (ROP) of 1,3‐benzoxazines is investigated. The significant reduction observed for the ROP temperature is related to the nucleophilicity of counterions and found to show a general trend as I− > Br− > Cl−, as studied by differential scanning calorimetry and Fourier transform infrared spectroscopy. Moreover, the latent character of the amine salts is also demonstrated by tracking the benzoxazine–amine sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 55 publications
2
31
0
Order By: Relevance
“…And recently, latent catalyst systems come into prominence since these catalysts are dormant at room temperature, but activated upon heating, making it easier to prepare catalyst‐benzoxazine formulations that are suitable for long term storage. Some amines, ammonium and lithium salts were used as latent catalysts that successfully initiated the polymerization . However, these compounds generally act as nucleophiles and the proposed initiation step is considered to be different than the usual benzoxazine polymerization mechanism.…”
Section: The Journey Of Phenolicsmentioning
confidence: 99%
See 1 more Smart Citation
“…And recently, latent catalyst systems come into prominence since these catalysts are dormant at room temperature, but activated upon heating, making it easier to prepare catalyst‐benzoxazine formulations that are suitable for long term storage. Some amines, ammonium and lithium salts were used as latent catalysts that successfully initiated the polymerization . However, these compounds generally act as nucleophiles and the proposed initiation step is considered to be different than the usual benzoxazine polymerization mechanism.…”
Section: The Journey Of Phenolicsmentioning
confidence: 99%
“…Some amines, ammonium and lithium salts were used as latent catalysts that successfully initiated the polymerization. [76][77][78][79] However, these compounds generally act as nucleophiles and the proposed initiation step is considered to be different than the usual benzoxazine polymerization mechanism.…”
Section: Strategies In Designing Phenolics For Service Toolsmentioning
confidence: 99%
“…Thus, several strategies were developed in order to reduce the polymerization temperature by designing monomers with self-catalytic effect on the ROP as the –COOH and –OH groups showed effective contribution to accelerate the process [ 5 , 9 , 10 , 11 , 12 ]. However, the most significant results were obtained when extra-catalysts were employed such as cyanuric chloride [ 13 ], amines [ 14 ], sulfonates [ 15 ], lithium [ 16 ], and amine salts [ 17 , 18 ] that not only lower the ROP temperature but contribute to prolongation of the product life storage also. Recently, studies showed that incorporation of graphene oxide (GO) into polymer-based composite formulations significantly contribute to reduction of polymerization temperature [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Liu et al observed that LiI was especially efficient [37]. Recently, Akkus et al highlighted that for amine salts, the nucleophilicity of the counterion had high impact, and they observed that the anion I − exhibited the best catalytic behavior [38]. Organic-based catalysts such as acetylacetonato complexes with iron, manganese, or cobalt, sulfonates such as para-toluene sulfonate, or organic oniums such as sulfonium hexafluoroantimonates were also found to be highly efficient for promoting the polymerization of benzoxazine precursors at a lower temperature [39][40][41].…”
Section: Introductionmentioning
confidence: 99%